What Contribution can Regional Planning Capable Make to the Implementation of a „Sustainable” Approach to Securing the Supply of Raw Materials? The example of sand and gravel - Mühl, Gerald (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
The current paradigm guiding regional planning is that of sustainable spatial development. Among the challenges this poses is the task of both controlling the extraction of and securing the supply of raw materials found close to the surface. In the context of this extremely fraught task, this article discusses rules for dealing with natural assets. It is increasingly coming to be accepted that, in some form or other, natural resources have to be managed. Since the function of spatial planning consists in ordering and safeguarding types of land use, the contribution it might possibly make to resource management would appear initially to be negligible indeed. However, with regard to certain raw materials (sand and gravel) there is considerable scope for action within spatial planning.
Keywords: Article